THE EMBEDED DELIBERATIVE AND REALIGNMENT OF THE COMPASS DIRECTION OF LINGUAL ORBITAL ARGUMENTS - Eaktiffaa Mutar Shurbak-Gayim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The embedded deliberative, with its levels and analytical mechanisms, is an integrated and interdisciplinary method; therefore, it could be used in the analysis of many texts of influential and persuasive dimensions, with what gives the deliberative trading dealings richness in terms of fruitful procedures and satisfactory results, especially in the heritage texts that have harmonic conceptualism levels, and those that exist on vast areas of speech classes, another thing that distinguishes this theory is that the embedded deliberative opposes the dependence of the literal meaning alone in clarifying the meaning of the words. Therefore, the statement is fulfilled in stating the meanings contained in these texts. Starting from the literal meaning represented by its significance in the speech towards its interpretation in a manner consistent with the position of the speech, and as it serves her argumentative, especially since the analysis of the sayings in the embedded deliberative is based on a set of linguistic data and rhetorical data. Hence the importance of this research: Because it deals with a theory that does not seem limited to one dimension, but rather it branches off, and is still in the process of trimming and modification.